One major facilitator superfamily transporter is responsible for propionic acid tolerance in Pseudomonas putida KT2440. Issue 2 (31st May 2020) - Ma, Chao; Mu, Qingxuan; Xue, Yubin; Xue, Yanfen; Yu, Bo; Ma, Yanhe
Summary: Propionic acid (PA) has been widely used as a food preservative and chemical intermediate in the agricultural and pharmaceutical industries. Environmental and friendly biotechnological production of PA from biomass has been considered as an alternative to the traditional petrochemical route. However, because PA is a strong inhibitor of cell growth, the biotechnological host should be not only able to produce the compound but the host should be robust. In this study, we identified key PA tolerance factors in Pseudomonas putida KT2440 strain by comparative transcriptional analysis in the presence or absence of PA stress. The identified major facilitator superfamily (MFS) transporter gene cluster of PP_1271, PP_1272 and PP_1273 was experimentally verified to be involved in PA tolerance in P. putida strains. Overexpression of this cluster improved tolerance to PA in a PA producing strain, what is useful to further engineer this robust platform not only for PA synthesis but for the production of other weak acids. Abstract : In this study, one major facilitator superfamily transporter (MFS2, locus tags of PP_1271‐PP_1273), but not MFS1 (locus tag of PP_0503), is beneficial to propionate tolerance in Pseudomonas putida strain KT2440. Thus, this study revealed the key genes responsible for PA tolerance in P. putida strains and provided the useful information to further engineer robust strains for PA production.